A scoping review of endoscopic and robotic techniques for lateral neck dissection in thyroid cancer - Woods, Alexis L.; Campbell, Michael J.; Graves, Claire E. (Frontiers in Oncology, 2024)
Introduction: Lateral neck dissection (LND) in thyroid cancer has traditionally been performed by a transcervical technique with a large collar incision. With the rise of endoscopic, video-assisted, and robotic techniques for thyroidectomy, minimally invasive LND is now being performed more frequently, with better cosmetic outcomes. Methods: The purpose of this paper is to review the different minimally invasive and remote access techniques for LND in thyroid cancer. A comprehensive literature review was performed using PubMed and Google Scholar search terms "thyroid cancer" and "lateral neck dissection" and "endoscopy OR robot OR endoscopic OR videoassisted." Results: There are multiple surgical options now available within each subset of endoscopic, video-assisted, and robotic LND. The approach dictates the extent of the LND but almost all techniques access levels II-IV, with variability on levels I and V. This review provides an overview of the indications, contraindications, surgical and oncologic outcomes for each technique.Discussion: Though data remains limited, endoscopic and robotic techniques for LND are safe, with improved cosmetic results and comparable oncologic and surgical outcomes. Similar to patient selection in minimally invasive thyroidectomy, it is important to consider the extent of the LND and select appropriate surgical candidates.